" Propuesta de un módulo de Jardines Verticales para espacios Arquitectónicos en la ciudad de Riobamba. - Rivadeneira Torres, Eduardo Vinicio (2016)
Vertical gardens have allowed transporting the jungles and forests to monotone cities which uses the "concrete" as the main material for their buildings. Although, the vertical gardens are those associated with terms like "esthetic" and "beauty" emerges a new concept of sustainable character which attempts to balance economic, social and ecological aspect so that a perfect trilogy that allows a responsible interdependence of these forms. This research aims to "improve the aesthetics, perception and livability of the selected building in the weight matrix (Consejo Provincial); by the proposed of application vertical gardens modules in architectural spaces ", this means reduced energy consumption and improve environmental quality. First, a detailed analysis was conducted, also proposals and historical references that helped helped to clarify and better understand the evolution, the operating and the impact of vertical gardens in buildings. Thus, the necessary guidelines have generated which led to the development of observational and subsequent implementation in different buildings in Riobamba, which have been considered suitable for the use of vertical gardens. Subsequently it has developed the respective weighting matrix that identified the building "Consejo Provincial de Chimborazo" as most suitable for implementing modular architecture vertical gardens. Additional, vertical garden module was designed and consequently the architectural proposal was made by applying several modules in facades and interiors of the building "Consejo Provincial de Chimborazo". Finally, the thermal and acoustic analysis carried out using environmental simulation software Ecotect, which yielded favorable results with respect to the application of modular vertical gardens takes place; similarly, the surveys users of the building showed satisfactory results. The proposed application of modular vertical gardening in the building, supports an increase of landscaped urban area and guarantee improved livability by providing thermal insulation, reducing the room temperature at an average of 1,785 ° C per day, which translates in a decrease of 0.051 ° C per day for each module vertical garden. Likewise, it provides acoustic insulation, absorbing sound waves of a frequency of 130Hz, which implies a reduction of the reverberation time.